Thank you for the opportunity to help you with your question!

To find inverse of the given function; let f(x)=y

y=6-5x

5x=6-y

x=(6-y)/5

interchanging y and x, we get

y=(6-x)/5

this is the inverse function - f^-1(x) = (6-x)/5

Now, put x=-39

f^-1(-39) = [6-(-39)]/5

f^-1(-39) = 45/5

f^-1(-39)=9

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up